Relationship between dietary pattern and depressive symptoms: an international multicohort study - Hanzhang Wu; Yeqing Gu; Ge Meng; Qing Zhang; Li Liu; Hongmei Wu; Shunming Zhang; Tingjing Zhang; Xuena Wang; Juanjuan Zhang; Shaomei Sun; Xing Wang; et al. (BMC, 2023)
Abstract Background Several previous studies have shown that dietary patterns are associated with the incidence of depressive symptoms. However, the results have been inconsistent. This study aimed to prospectively investigate the association between dietary patterns and the risk of depressive symptoms in two large cohort studies. Methods The Tianjin Chronic Low-grade Systemic Inflammation and Health (TCLSIH) cohort study included a total of 7,094 participants living in Tianjin, China from 2013 to 2019, and the UK Biobank cohort study includes 96,810 participants who were recruited from 22 assessment centers across the UK taken between 2006 and 2010. All participants were free of a history of cardiovascular disease (CVD), cancer, and depressive symptoms at baseline. Dietary patterns at baseline were identified with factor analysis based on responses to a validated food frequency questionnaire in TCLSIH or Oxford WebQ in UK Biobank. Depressive symptoms were evaluated using the Chinese version of the Zung Self-Rating Depression Scale (SDS) in TCLSIH or hospital inpatient records in UK Biobank. Cox proportional hazards regression models were used to estimate the association between dietary patterns and depressive symptoms. Results A total of 989, and 1,303 participants developed depressive symptoms during 17,410 and 709,931 person-years of follow-up. After adjusting for several potential confounders, the multivariable HRs (95% CIs) of the depressive symptoms were 0.71 (0.57, 0.88) for traditional Chinese dietary pattern, 1.29 (1.07, 1.55) for processed animal offal included animal food dietary pattern, and 1.22 (1.02, 1.46) for sugar rich dietary pattern in TCLSIH (all Q4 vs Q1). In the UK Biobank, the HRs (95% CIs) of depressive symptoms were 1.39 (1.16, 1.68) for processed food dietary pattern (Q4 vs Q1), 0.90 (0.77, 1.00) for healthy dietary pattern (Q3 vs Q1), and 0.89 (0.75, 1.05) for meat dietary pattern (Q4 vs Q1) in the final adjusted model. Conclusion Dietary patterns rich in processed foods were associated with a higher risk of depressive symptoms, and following a traditional Chinese dietary pattern or healthy dietary pattern was associated with a lower risk of depressive symptoms, whereas meat dietary pattern was not associated.